(Ne)priznavanje privilegija zoper samoobtožbo pravnim osebam s poudarkom na enoosebni gospodarski družbi - Vavken, Luka (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2024)
The aticle analyses whether, in punitive proceedings, the right to the privilege against self-incrimination should be granted not only to natural but also to legal persons. Since the prosecution of criminal and minor offences involving legal persons depends more on material (i.e. non-verbal) evidence than does the prosecution of natural persons, the introductory sections of the discussion address the scope of the privilege against self-incrimination. In contemporary legal dogmatics and case law, this privilege does not cover only testimonial evidence but also material or documentary evidence over which the suspect has control. Because, due to the system of limited accessory liability of legal persons, the punitive allegation against the natural (responsible) individual within the legal entity is generally substantively intertwined with the allegation against the legal person, the privilege against self-incrimination enjoyed by the alleged perpetrator of a criminal or minor offence often simultaneously protects the legal person from testifying and submitting documentary material to its detriment. However, this is not always the case. The author argues that, in such situations, legal persons should themselves be granted an independent right to the privilege against self-incrimination. This is particularly so when the suspected or accused entity is a single-member company, in which case granting the privilege against self-incrimination effectively protects its "owner" - the sole shareholder - from testifying (acting) to their own detriment.
Keywords: enoosebna družba z omejeno odgovornostjo; fair trial guarantees; jamstva poštenega postopka; legal person; liability of legal persons for criminal offences; liability of legal persons for minor offences; limited accessory liability; limitirana akcesorna odgovornost; odgovornost pravnih oseb za kazniva dejanja; odgovornost pravnih oseb za prekrške; pravna oseba; privilege against self-incrimination; privilegij zoper samoobtožbo; single-member limited liability company